Pengembangan Sumber Daya Manusia Melalui Pengenalan Konsep DISC pada Remaja Panti Asuhan Putra Setia Yayasan Rukun Istri Sejahtera, Jakarta Pusat - Wahid Akbar Basudani; Muhammad Abdullah; Ida Zuniarti; Valentine Theresia Simamora (Indonesian Journal of Society Engagement, 2023)
This Community Service activity aims to provide socialization and training for teenagers who are under the guidance of the Putra Setia Orphanage, the Rukun Istri Sejahtera Foundation, Central Jakarta where these teenagers need knowledge about personality development with the DISC concept. The method used is to give lectures or direct presentation of material. The DISC concept consists of Dominant, Influence, Steady and Compliant. By knowing the DISC concept, these teenagers can get to know themselves in an effort to develop personality and increase human resources.